English Catholicism, 1558-1642 - Dures, Alan (Seminar studies, 2022)
"Newly revised and updated, the second edition of English Catholicism 1558-1642 explores the position of Catholics in early modern English society, their political significance, and the internal politics of the Catholic community. Co-authored with Francis Young, this volume has been updated to include recent developments in the historiography of English Catholicism. It is a useful introduction for all undergraduate students interested in the English Reformation and early modern English history"--